Alicyclic epoxy resin material with saccharide dirt self-degradation function and preparation method thereof

By introducing alicyclogenic epoxy resin material of photocatalytic microcapsules into the insulating material, the problem of degradation of hydrophobic properties of insulating materials caused by contamination of sugar organic matter is solved, and the self-cleaning function and long-term stability of the surface of the material is achieved.

CN119752106AActive Publication Date: 2025-04-04TIANFU YONGXING LAB
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411938264.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In environments such as sugarcane planting areas, a large amount of sugar organic matter is easily attached to the surface of the insulation material outside the transmission line, resulting in a decrease in the hydrophobic performance of the insulation material and easily causing dangerous problems such as discharge along the surface.

Method used

Alicyclophago epoxy resin material with self-degradation of sugar filth is used, which includes 90-120 parts of aliphatic epoxy resin, 70-90 parts of curing agent, 5-30 parts of photocatalytic microcapsules, 3-10 parts of polydimethylsiloxane, 2-10 parts of POSS and 0.5-2 parts of curing accelerator. Photocatalytic microcapsules catalyze degrade organic contamination of sugars by releasing nanocatalysts, realizing the self-cleaning function of the material surface.

Benefits of technology

It effectively maintains the stable hydrophobic properties of the insulating material, avoids the risk of discharge along the surface, and extends the service life of the insulating material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752106A_ABST
    Figure CN119752106A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of insulating resin, and aims to solve the problem that dangers such as creeping discharge are easily caused due to the fact that hydrophobicity of an external insulating material for power equipment is severely reduced under the application scene that a large amount of saccharide organic matter dirt is contained in the environment. The alicyclic epoxy resin material is prepared from the following components in parts by mass: 90 to 120 parts of aliphatic epoxy resin, 70 to 90 parts of a curing agent, 5 to 30 parts of photocatalytic microcapsules, 3 to 10 parts of polydimethylsiloxane, 2 to 10 parts of POSS (Polyhedral Oligomeric Silsesquioxane) and 0.5 to 2 parts of a curing accelerator. According to the invention, the epoxy resin matrix is subjected to structural modification treatment, and the free organic silicon dispersed phase with stable size and the microcapsule of which the inner core is embedded with the photocatalyst are introduced into the epoxy resin matrix, so that the epoxy resin material can be endowed with excellent hydrophobicity and capability of self-degrading saccharide organic matter dirt at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of insulating resins, and in particular to an alicyclic epoxy resin material with a sugar pollution self-degradation function and a preparation method thereof. Background Art

[0002] Insulating materials, also known as dielectrics, refer to materials that are non-conductive or extremely conductive under the allowable voltage. They are commonly found in electrical equipment and are used to isolate charged conductors of different potentials so that current can flow along a certain path. They also play the role of support, fixation, heat dissipation, energy storage, moisture and mildew resistance. With the development of power systems towards high voltage, large capacity, and long-distance power transmission, the performance requirements of insulating materials in power systems are also increasing. They not only need to have excellent electrical insulation performance and mechanical strength, but also need to maintain long-term stable hydrophobicity and anti-pollution flashover capabilities under complex and changing environmental conditions.

[0003] Traditional power insulation materials mostly use silicone rubber materials, or introduce elements such as fluorine into silicone rubber materials to improve and enhance the environmental adaptability of the materials. However, silicone rubber materials also face many challenges in special application environments. For example, in scenes with similar environmental characteristics such as sugarcane planting areas, the surface of the insulation material outside the transmission line is prone to contamination containing a large amount of sugar organic matter. These sugar organic contaminations are not only highly hygroscopic, but also hinder the migration of hydrophobic small molecules in silicone rubber materials, causing its hydrophobic performance to drop sharply, and then causing surface discharge, which seriously threatens the safe operation of the transmission line.

[0004] In response to the problems existing in similar application scenarios, there is an urgent need for an insulating material that can effectively overcome the technical difficulty of the adverse effects of sugar substances attached to the surface of the material on the insulating material. Summary of the invention

[0005] The purpose of the present invention is to address the problem that in application scenarios where the environment contains a large amount of sugar organic pollution, the hydrophobicity of the outer surface insulation material used for power equipment is seriously reduced, which can easily cause dangerous problems such as surface discharge.

[0006] The present invention is achieved through the following technical solutions:

[0007] The invention provides an alicyclic epoxy resin material with a sugar pollution self-degradation function, which comprises, by weight, 90-120 parts of aliphatic epoxy resin, 70-90 parts of curing agent, 5-30 parts of photocatalytic microcapsules, 3-10 parts of polydimethylsiloxane, 2-10 parts of POSS and 0.5-2 parts of curing accelerator.

[0008] Preferably, the method for preparing the photocatalytic microcapsules comprises the following steps:

[0009] A1 mixes urea and formaldehyde, adjusts the pH value to 8.5-9.0, and heats the mixture to react, thereby forming a urea-formaldehyde prepolymer solution;

[0010] A2: placing the nanocatalyst in deionized water, adding sodium dodecyl sulfate, and ultrasonically dispersing to obtain a water-in-oil emulsion;

[0011] A3: adding the urea-formaldehyde prepolymer solution to the water-in-oil emulsion, adjusting the pH value to 3.5-4.5, stirring, then heating, standing and curing to obtain the photocatalytic microcapsules.

[0012] Preferably, in step A1, the mixture is heated to 75-95° C. and stirred for reaction for 15-35 min; in step A3, the mixture is heated to 50-60° C. and allowed to stand for curing for 1-1.5 h.

[0013] Preferably, the nanocatalyst comprises any one or more of platinum, cobalt or titanium dioxide.

[0014] The above-mentioned photocatalytic microcapsules are introduced into epoxy resin. When sugar contaminants are attached to the surface of the alicyclic epoxy composite insulating material, the microcapsules inside the material release nanocatalysts, and the nanocatalysts migrate to the surface to catalyze the degradation of sugar organic contaminants, thereby realizing the self-cleaning function of the material surface, removing obstacles that inhibit the migration of hydrophobic small molecules, and maintaining long-term hydrophobic performance stability; and the nanocatalysts released by the microcapsules inside the material have excellent resistance to ultraviolet aging, can absorb ultraviolet light, neutralize photodegradation free radicals, and extend the outdoor service life of organic external insulating materials.

[0015] Preferably, the aliphatic epoxy resin includes one or more of 3,4-epoxycyclohexylcarboxylate, 3,4-epoxycyclohexylcarboxylate, bis((3,4-epoxycyclohexyl)methyl)adipate, tetrahydroindene diepoxide, 3,4-epoxycyclohexylcarboxylate acrylate, 3,4-epoxycyclohexylcarboxylate methacrylate, 3,4-epoxycyclohexylcarboxylate acrylate or vinylcyclohexene dioxide.

[0016] Preferably, the POSS comprises one or more of a hexasiloxane cage, an octasiloxane cage or a dodecasiloxane cage.

[0017] The present invention also provides a method for preparing the above-mentioned alicyclic epoxy resin material having the function of self-degradation of sugar pollution, comprising the following steps:

[0018] S1: firstly mix aliphatic epoxy resin and POSS according to the amount, add peroxide, and heat to react; then add polydimethylsiloxane, curing agent and curing accelerator, mix, and then place in a vacuum environment and stir to obtain alicyclic epoxy resin intermediate emulsion;

[0019] S2 adds the photocatalytic microcapsules to the alicyclic epoxy resin intermediate emulsion, stirs and disperses, pours, heats and solidifies, and cools and demolds to obtain the alicyclic epoxy resin material with the function of self-degradation of sugar pollution. The microcapsule wall and the epoxy resin have excellent interface bonding properties, which can avoid the problems of reduced mechanical and insulation properties caused by poor microscopic interface properties between the directly added catalyst and the epoxy matrix.

[0020] In the present invention, a polydimethylsiloxane dispersed phase with stable micro-nano size can be formed inside the alicyclic epoxy resin, and the free organic silicon small molecules inside the dispersed phase can migrate to the surface of the material, giving the material excellent hydrophobic and migration properties.

[0021] Preferably, in step S1, the temperature is heated to 60-100° C. and the reaction is carried out for 3-12 hours.

[0022] Preferably, when heating is started, peroxide is added at a uniform rate at the same time, and the addition time of peroxide is 40-60 minutes.

[0023] Preferably, in step S2, the temperature is heated to 100-120°C and the temperature is kept constant for curing for 5-8 hours.

[0024] The technical solution of the present invention has the following beneficial effects:

[0025] The present invention adopts alicyclic epoxy resin with excellent leakage resistance, which can effectively resist surface discharge ablation and extend the service life of the epoxy resin insulating matrix in the above environment; and the epoxy resin matrix is ​​structurally modified, and then a dimensionally stable free silicone dispersed phase and microcapsules with photocatalysts embedded in the inner core are introduced therein, which can simultaneously give the epoxy resin material excellent hydrophobicity and the ability to self-degrade sugar organic contamination.

[0026] Among them, the micro-interface of the microcapsule wall material and the epoxy resin matrix is ​​well bonded, and without adding other additives, problems such as interface incompatibility and uneven dispersion during mixing or application can be avoided, that is, the influence of the added additives on the mechanical properties and insulation properties of the material can be avoided; in the photocatalytic microcapsules, TiO2 can not only be used as a photocatalytic substance, but also has excellent resistance to ultraviolet aging, which can further improve the service life of alicyclic epoxy resin insulating materials. In summary, the alicyclic epoxy resin material of the present invention can synergistically improve the hydrophobicity and mobility of epoxy resin insulating materials, the self-degradation ability of sugar organic pollution, weather resistance, etc., while reducing the cost of manual cleaning, and can effectively ensure the insulation and safety of power equipment whose surface is easily attached with sugar organic pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram of the morphology of sugar pollution accumulation in Example 1;

[0028] Figure 2 This is a schematic diagram of the morphology of the photocatalytic microcapsules in Example 1 after release to degrade sugar pollution. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. Where specific conditions are not specified in the embodiments, they are carried out under conventional conditions or conditions recommended by the manufacturer; where the manufacturers of the instruments, equipment, reagents and raw materials used are not specified, they are all conventional products that can be purchased commercially.

[0030] The present invention provides an alicyclic epoxy resin material having a sugar pollution self-degradation function, which comprises, by weight:

[0031] (1) 90-120 parts of an aliphatic epoxy resin, the aliphatic epoxy resin including but not limited to one or more of 3,4-epoxycyclohexylcarboxylate, 3,4-epoxycyclohexylcarboxylate, bis((3,4-epoxycyclohexyl)methyl)adipate, tetrahydroindene diepoxide, 3,4-epoxycyclohexylcarboxylate acrylate, 3,4-epoxycyclohexylcarboxylate methacrylate, 3,4-epoxycyclohexylcarboxylate acrylate, and vinylcyclohexene dioxide;

[0032] (2) 70-90 parts of curing agent;

[0033] (3) 0.5-2 parts of curing accelerator;

[0034] (4) 3-7 parts of polydimethylsiloxane, including but not limited to one or more of epoxy-terminated polydimethylsiloxane, hydroxy-terminated polydimethylsiloxane, amino-terminated polydimethylsiloxane and vinyl polydimethylsiloxane, and the molecular weight of the polydimethylsiloxane is 500-1000 g / mol, which can give the material excellent hydrophobicity and mobility;

[0035] (5) 2-12 parts of POSS, POSS including but not limited to one or more of hexasiloxane cage, octasiloxane cage and dodecasiloxane cage;

[0036] (6) 5-30 parts of photocatalytic microcapsules, which contain photocatalysts, including but not limited to one or more of platinum, cobalt and titanium dioxide, etc., which have the ability to efficiently catalyze the degradation of organic matter and can decompose sugar organic pollutants, thereby removing surface hygroscopic pollutants and maintaining the hydrophobic properties of the material.

[0037] In the present invention, the above-mentioned photocatalytic microcapsules are embedding materials with urea-formaldehyde resin as wall material and TiO2 as core material, and can be prepared by in-situ polymerization method, which specifically includes the following steps:

[0038] (1) urea and formaldehyde are mixed at a molar ratio of 1:1.5-3, and the mixed solution is adjusted to be alkaline, preferably with a pH value of 8.5-9.0, heated to 75-95° C., and stirred for reaction for 15-35 minutes to form a urea-formaldehyde prepolymer solution;

[0039] (2) uniformly dispersing the nanocatalyst in deionized water, adding sodium dodecyl sulfate, and subjecting to ultrasonic treatment to obtain a stable water phase, and then slowly injecting the water phase into the oil phase and stirring to form an oil-in-water emulsion;

[0040] (3) adding the urea-formaldehyde prepolymer solution prepared above to the water-in-oil emulsion, adding an acidic catalyst such as dilute hydrochloric acid, adjusting the pH value of the material to 3.5-4.5, promoting the polymerization of urea-formaldehyde at the emulsion interface, and gradually forming microcapsules with TiO2 as the core material; then heating to 50-60°C, standing for 1-1.5 hours, and allowing the surface to solidify to form a capsule wall layer, separating the microcapsules by centrifugation or filtration, washing the residual impurities, and drying to obtain photocatalytic microcapsules with stable morphology and structure.

[0041] In the present invention, the preparation method of the alicyclic epoxy resin material having the function of self-degradation of sugar pollution comprises the following steps:

[0042] (1) Preparation of alicyclic epoxy resin emulsion

[0043] The aliphatic epoxy resin and POSS are mixed according to the amount, heated to 60-100°C, and reacted for 3-12 hours, during which peroxide is continuously added at a uniform speed, and the peroxide addition time is 40-60 minutes; then a curing agent, a curing accelerator and polydimethylsiloxane are added, mixed, and fully stirred until a uniform emulsion is formed; the uniformly mixed emulsion is placed in a vacuum environment, stirred, and residual air in the mixed emulsion is removed, so as to obtain a hydrophobic alicyclic epoxy resin intermediate emulsion.

[0044] Among them, removing residual air in the emulsion through a vacuum environment can prevent bubbles from being generated after the material is cured.

[0045] (2) Preparation of alicyclic epoxy resin materials with self-degradation function of sugar pollution

[0046] The photocatalytic microcapsules are added to the alicyclic epoxy resin intermediate emulsion prepared above, and stirred evenly to make the photocatalytic microcapsules evenly dispersed in the emulsion; the stirred mixture is then poured into a mold, and then placed in a constant temperature oven, heated to 100-120°C, and kept warm for 5-8 hours to fully carry out the curing reaction; after curing and molding, the mold is taken out, cooled to room temperature, and then demolded to obtain an alicyclic epoxy resin material with the function of self-degradation of sugar pollution.

[0047] Example 1

[0048] Step 1: Take urea and formaldehyde in a molar ratio of 1:2 respectively, mix them, and add triethanolamine dropwise until the pH value of the mixed solution is adjusted to about 8.6, then heat it to about 80°C, keep stirring at 120rpm, react for 20min, and obtain a urea-formaldehyde prepolymer solution; then take TiO2 nanoparticles, place them in an equal volume of deionized water, add 22wt% sodium dodecyl sulfate, and ultrasonically disperse them for 45min to obtain an oil-in-water emulsion; add the urea-formaldehyde prepolymer solution to the oil-in-water emulsion, add 1M hydrochloric acid solution dropwise until the pH value of the mixed solution is adjusted to about 4.0, then heat it to about 53°C, let it stand for 1.2h, separate the microcapsules by centrifugation, rinse them with deionized water, and dry them to obtain photocatalytic microcapsules.

[0049] Step 2: Take 3,4-epoxycyclohexylcarboxylate, methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, vinyl polydimethylsiloxane, dodecylsiloxane cage and the photocatalytic microcapsules prepared above in a mass ratio of 98:72:1.5:5.5:6.5:22 respectively and set aside.

[0050] Step 3: First, mix 3,4-epoxycyclohexylcarboxylate with dodecylsiloxane cage, heat to 80°C, and react for 8 hours, during which hydrogen peroxide is added continuously at a uniform speed, and the addition time of hydrogen peroxide is 45 minutes; then add methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane, mix, and stir thoroughly until a uniform emulsion is formed; place the uniformly mixed emulsion in a vacuum environment, stir for 15 minutes, and obtain a hydrophobic alicyclic epoxy resin intermediate emulsion; add photocatalytic microcapsules to the above-mentioned alicyclic epoxy resin intermediate emulsion, stir evenly, and then pour it into a mold, place it in an oven, heat to 105°C, and keep it at a constant temperature for 6.5 hours. After curing and molding, take out the mold, cool to room temperature, and demold to obtain an alicyclic epoxy resin material.

[0051] Example 2

[0052] Step 1: Take urea and formaldehyde in a molar ratio of 1:2 respectively, mix them, and add triethanolamine dropwise until the pH value of the mixed solution is adjusted to about 8.6, then heat it to about 80°C, keep stirring at 120rpm, react for 20min, and obtain a urea-formaldehyde prepolymer solution; then take TiO2 nanoparticles, place them in an equal volume of deionized water, add 22wt% sodium dodecyl sulfate, and ultrasonically disperse them for 45min to obtain an oil-in-water emulsion; add the urea-formaldehyde prepolymer solution to the oil-in-water emulsion, add 1M hydrochloric acid solution dropwise until the pH value of the mixed solution is adjusted to about 4.0, then heat it to about 53°C, let it stand for 1.2h, separate the microcapsules by centrifugation, rinse them with deionized water, and dry them to obtain photocatalytic microcapsules.

[0053] Step 2: Take 3,4-epoxycyclohexylcarboxylate, methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, vinyl polydimethylsiloxane, dodecylsiloxane cage and the photocatalytic microcapsules prepared above in a mass ratio of 98:72:1.5:5.5:2.5:6 respectively and set aside.

[0054] Step 3: First, mix 3,4-epoxycyclohexylcarboxylate with dodecylsiloxane cage, heat to 80°C, and react for 8 hours, during which hydrogen peroxide is added continuously at a uniform speed, and the addition time of hydrogen peroxide is 45 minutes; then add methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane, mix, and stir thoroughly until a uniform emulsion is formed; place the uniformly mixed emulsion in a vacuum environment, stir for 15 minutes, and obtain a hydrophobic alicyclic epoxy resin intermediate emulsion; add photocatalytic microcapsules to the above-mentioned alicyclic epoxy resin intermediate emulsion, stir evenly, and then pour it into a mold, place it in an oven, heat to 105°C, and keep it at a constant temperature for 6.5 hours. After curing and molding, take out the mold, cool to room temperature, and demold to obtain an alicyclic epoxy resin material.

[0055] Example 3

[0056] Step 1: Take urea and formaldehyde in a molar ratio of 1:2 respectively, mix them, and add triethanolamine dropwise until the pH value of the mixed solution is adjusted to about 8.6, then heat it to about 80°C, keep stirring at 120rpm, react for 20min, and obtain a urea-formaldehyde prepolymer solution; then take TiO2 nanoparticles, place them in an equal volume of deionized water, add 22wt% sodium dodecyl sulfate, and ultrasonically disperse them for 45min to obtain an oil-in-water emulsion; add the urea-formaldehyde prepolymer solution to the oil-in-water emulsion, add 1M hydrochloric acid solution dropwise until the pH value of the mixed solution is adjusted to about 4.0, then heat it to about 53°C, let it stand for 1.2h, separate the microcapsules by centrifugation, rinse them with deionized water, and dry them to obtain photocatalytic microcapsules.

[0057] Step 2: Take 3,4-epoxycyclohexylcarboxylate, methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, vinyl polydimethylsiloxane, dodecylsiloxane cage and the photocatalytic microcapsules prepared above in a mass ratio of 105:72:0.65:10:2.5:6.2 respectively and set aside.

[0058] Step 3: First, mix 3,4-epoxycyclohexylcarboxylate with dodecylsiloxane cage, heat to 80°C, and react for 8 hours, during which hydrogen peroxide is added continuously at a uniform speed, and the addition time of hydrogen peroxide is 45 minutes; then add methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane, mix, and stir thoroughly until a uniform emulsion is formed; place the uniformly mixed emulsion in a vacuum environment, stir for 15 minutes, and obtain a hydrophobic alicyclic epoxy resin intermediate emulsion; add photocatalytic microcapsules to the above-mentioned alicyclic epoxy resin intermediate emulsion, stir evenly, and then pour it into a mold, place it in an oven, heat to 105°C, and keep it at a constant temperature for 6.5 hours. After curing and molding, take out the mold, cool to room temperature, and demold to obtain an alicyclic epoxy resin material.

[0059] Example 4

[0060] Step 1: Take urea and formaldehyde in a molar ratio of 1:2, mix them, and add triethanolamine dropwise until the pH value of the mixed solution is adjusted to about 8.6, then heat to about 80°C, continue stirring at 120rpm, react for 20min, and obtain a urea-formaldehyde prepolymer solution; then take cobalt powder, place it in an equal volume of deionized water, add 22wt% sodium dodecyl sulfate, and ultrasonically disperse it for 45min to obtain an oil-in-water emulsion; add the urea-formaldehyde prepolymer solution to the oil-in-water emulsion, add 1M hydrochloric acid solution dropwise until the pH value of the mixed solution is adjusted to about 4.0, then heat to about 53°C, let it stand for 1.2h, separate the microcapsules by centrifugation, rinse with deionized water, and dry to obtain photocatalytic microcapsules.

[0061] Step 2: Take 3,4-epoxycyclohexylcarboxylate, methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, vinyl polydimethylsiloxane, dodecylsiloxane cage and the photocatalytic microcapsules prepared above in a mass ratio of 98:72:1.5:5.5:6.5:22 respectively and set aside.

[0062] Step 3: First, mix 3,4-epoxycyclohexylcarboxylate with dodecylsiloxane cage, heat to 80°C, and react for 8 hours, during which hydrogen peroxide is added continuously at a uniform speed, and the addition time of hydrogen peroxide is 45 minutes; then add methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane, mix, and stir thoroughly until a uniform emulsion is formed; place the uniformly mixed emulsion in a vacuum environment, stir for 15 minutes, and obtain a hydrophobic alicyclic epoxy resin intermediate emulsion; add photocatalytic microcapsules to the above-mentioned alicyclic epoxy resin intermediate emulsion, stir evenly, and then pour it into a mold, place it in an oven, heat to 105°C, and keep it at a constant temperature for 6.5 hours. After curing and molding, take out the mold, cool to room temperature, and demold to obtain an alicyclic epoxy resin material.

[0063] Example 5

[0064] Step 1: Take urea and formaldehyde in a molar ratio of 1:2 respectively, mix them, and add triethanolamine dropwise until the pH value of the mixed solution is adjusted to about 8.6, then heat it to about 80°C, keep stirring at 120rpm, react for 20min, and obtain a urea-formaldehyde prepolymer solution; then take TiO2 nanoparticles, place them in an equal volume of deionized water, add 22wt% sodium dodecyl sulfate, and ultrasonically disperse them for 45min to obtain an oil-in-water emulsion; add the urea-formaldehyde prepolymer solution to the oil-in-water emulsion, add 1M hydrochloric acid solution dropwise until the pH value of the mixed solution is adjusted to about 4.0, then heat it to about 53°C, let it stand for 1.2h, separate the microcapsules by centrifugation, rinse them with deionized water, and dry them to obtain photocatalytic microcapsules.

[0065] Step 2: Take 3,4-epoxycyclohexylcarboxylate, methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, vinyl polydimethylsiloxane, dodecylsiloxane cage and the photocatalytic microcapsules prepared above in a mass ratio of 98:72:1.5:5.5:6.5:22 respectively and set aside.

[0066] Step 3: First, mix 3,4-epoxycyclohexylcarboxylate with dodecasiloxane cage, heat to 65°C, and react for 11.75 hours, during which hydrogen peroxide is added continuously at a uniform speed, and the addition time of hydrogen peroxide is 55 minutes; then add methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane, mix, and stir thoroughly until a uniform emulsion is formed; place the uniformly mixed emulsion in a vacuum environment and stir for 15 minutes to obtain a hydrophobic alicyclic epoxy resin intermediate emulsion; add photocatalytic microcapsules to the above-mentioned alicyclic epoxy resin intermediate emulsion, stir evenly, and then pour it into a mold, place it in an oven, heat to 105°C, and keep it at a constant temperature for 6.5 hours. After curing and molding, take out the mold, cool it to room temperature, and demold it to obtain an alicyclic epoxy resin material.

[0067] Comparative Example 1

[0068] Step 1: Take 3,4-epoxycyclohexylcarboxylate, methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane in a mass ratio of 98:72:1.5:12 respectively and set aside.

[0069] Step 2: First, mix 3,4-epoxycyclohexylcarboxylate with methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane, and stir them thoroughly until a uniform emulsion is formed; place the uniformly mixed emulsion in a vacuum environment, stir for 15 minutes, and obtain an epoxy resin intermediate emulsion; then pour it into a mold, place it in an oven, heat it to 105°C, and keep it at a constant temperature for 6.5 hours. After curing and forming, take out the mold, cool it to room temperature, and demold it to obtain an epoxy resin material.

[0070] Comparative Example 2

[0071] Step 2: Take 3,4-epoxycyclohexylcarboxylate, methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, vinyl polydimethylsiloxane and TiO2 nanoparticles in a mass ratio of 98:72:1.5:12:22 respectively and set aside.

[0072] Step three: first mix 3,4-epoxycyclohexylcarboxylate with methacrylic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol and vinyl polydimethylsiloxane, and stir thoroughly until a uniform emulsion is formed; place the uniformly mixed emulsion in a vacuum environment, stir for 15 minutes, and obtain an epoxy resin intermediate emulsion; add TiO2 nanoparticles to the above epoxy resin intermediate emulsion, stir evenly, and then pour it into a mold, place it in an oven, heat to 105°C, and keep it at a constant temperature for 6.5 hours. After curing and forming, take out the mold, cool to room temperature, and demold to obtain an alicyclic epoxy resin material.

[0073] Test example

[0074] (1) Figure 1 , Figure 2 As shown, there are respectively a schematic diagram of the morphology of the accumulation of sugar contaminants on the surface of the epoxy resin material, and a schematic diagram of the morphology of the degradation of sugar contaminants after the release of photocatalytic microcapsules. It can be clearly seen from the figure that the alicyclic epoxy resin material in the present invention can realize the self-cleaning function of the material surface through the degradation effect of the photocatalytic microcapsules contained in itself, remove the obstacles that inhibit the migration of hydrophobic small molecules, thereby maintaining the long-term stability of the hydrophobic performance.

[0075] (2) The epoxy resin materials prepared in Examples 1-5 and Comparative Examples 1-2 were used as samples to measure the hydrophobic properties of the materials at the initial stage and after treatment. The results are summarized in Table 1 below:

[0076] Table 1 Material properties of different samples at different stages

[0077]

[0078] Among them, the water contact angle is measured by dropping water on the surface of the epoxy resin material. The size of the contact angle can reflect the quality of the hydrophobicity; sugar treatment refers to the process of applying a 15% sucrose aqueous solution to the surface of the epoxy resin and leaving it at room temperature for 48 hours; the insulation performance is measured according to the requirements of GB / T1410-2006 "Test Method for Volume Resistivity and Surface Resistivity of Solid Insulating Materials".

[0079] The above measurement results show that, compared with Comparative Examples 1 to 2, the epoxy resin materials prepared by Examples 1 to 5 can maintain longer-lasting hydrophobicity and stable insulation performance in an environment with a large amount of sugar organic contamination. This means that the alicyclic epoxy resin material and the preparation method thereof proposed in the present invention can solve the problem that the hydrophobicity of the outer surface insulation material used in power equipment is seriously reduced, which easily causes dangerous problems such as surface discharge, in application scenarios where the environment contains a large amount of sugar organic contamination.

[0080] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An alicyclic epoxy resin material having a sugar pollution self-degradation function, characterized in that: Calculated by weight, the invention comprises 90-120 parts of aliphatic epoxy resin, 70-90 parts of curing agent, 5-30 parts of photocatalytic microcapsules, 3-10 parts of polydimethylsiloxane, 2-10 parts of POSS and 0.5-2 parts of curing accelerator.

2. The alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 1, characterized in that: The preparation method of the photocatalytic microcapsules comprises the following steps: A1 mixes urea and formaldehyde, adjusts the pH value to 8.5-9.0, and heats the mixture to react, thereby forming a urea-formaldehyde prepolymer solution; A2: placing the nanocatalyst in deionized water, adding sodium dodecyl sulfate, and ultrasonically dispersing to obtain a water-in-oil emulsion; A3: adding the urea-formaldehyde prepolymer solution to the water-in-oil emulsion, adjusting the pH value to 3.5-4.5, stirring, then heating, standing and curing to obtain the photocatalytic microcapsules.

3. The alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 2, characterized in that: In step A1, heat to 75-95° C. and stir to react for 15-35 minutes; in step A3, heat to 50-60° C. and stand to cure for 1-1.5 hours.

4. The alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 2, characterized in that: The nanocatalyst includes any one or more of platinum, cobalt or titanium dioxide.

5. The alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 1, characterized in that: The aliphatic epoxy resin includes one or more of 3,4-epoxycyclohexylcarboxylate, 3,4-epoxycyclohexylcarboxylate, bis((3,4-epoxycyclohexyl)methyl)adipate, tetrahydroindene diepoxide, 3,4-epoxycyclohexylcarboxylate acrylate, 3,4-epoxycyclohexylcarboxylate methacrylate, 3,4-epoxycyclohexylcarboxylate acrylate or vinylcyclohexene dioxide.

6. The alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 1, characterized in that: The POSS includes one or more of a hexasiloxane cage, an octasiloxane cage or a dodecasiloxane cage.

7. The method for preparing the alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to any one of claims 1 to 6, characterized in that: The steps include: S1: firstly mix aliphatic epoxy resin and POSS according to the amount, add peroxide, and heat to react; then add polydimethylsiloxane, curing agent and curing accelerator, mix, and then place in a vacuum environment and stir to obtain alicyclic epoxy resin intermediate emulsion; S2: adding the photocatalytic microcapsules into the alicyclic epoxy resin intermediate emulsion, stirring and dispersing, pouring, heating and curing, cooling and demolding, so as to obtain the alicyclic epoxy resin material with the function of self-degradation of sugar pollution.

8. The method for preparing the alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 7, characterized in that: In step S1, the temperature is heated to 60-100° C. and the reaction is carried out for 3-12 hours.

9. The method for preparing the alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 7, characterized in that: When heating begins, peroxide is added at a uniform rate, and the peroxide addition time is 40-60 minutes.

10. The method for preparing the alicyclic epoxy resin material having the function of self-degradation of sugar pollution according to claim 7, characterized in that: In step S2, the temperature is heated to 100-120°C and the temperature is kept to cure for 5-8 hours.

Citation Information

Patent Citations

  • POSS / epoxy nanometer hybrid material and preparation method and application thereof

    CN101985513A

  • Low dielectric constant polyhedral oligomeric silsesquioxane (POSS) / epoxy resin hybrid material and preparation method

    CN103146141A

  • Titanium dioxide microcapsule finishing agent and preparation method thereof

    CN107938316A

  • Epoxy resin composite insulating material and preparation method thereof

    CN109294166A

  • Method for preparing porous hydrophobic phosphate coating through titanium dioxide / urea resin microcapsules

    CN116870811A